The influence of motivation, working condition and organizational commitment on performance of civil service in Nigeria - Baba, Abubakar Isah (2019)
This study examined the influence of motivation (intrinsic and extrinsic), working conditions (physical environment, psychosocial and work-life balance) and organizational commitment (affective, normative, and continuance) on performance (task and contextual) with the mediating role of perceived organizational justice. Data were collected by administering 432 sets of questionnaire to civil servants in Sokoto State Nigeria. Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the hypotheses. The results provided support for some of the hypothesized relationships in the study. Specifically, intrinsic motivation, extrinsic motivation, and affective commitment were significantly and positively related to task and contextual performance. However, physical environment, psychosocial environment, work-life balance, normative and continuance commitment were significantly and negatively related to both task and contextual performance. Additionally, perceived organizational justice was significantly and positively related to task and contextual performance. More so, intrinsic and extrinsic motivation, psychosocial environment, affective and continuance commitments were significantly and positively related to perceived organizational justice. Furthermore, the results of mediation indicated that all three mediations at the construct level and 10 out of 16 dimensional hypotheses were significant. Taken together, these findings suggest that the variables are important in influencing an employee‟s task and contextual performance. As such, organizations should provide adequate motivation, a friendly working environment and commitment as well as fair treatment of workers with a view in enhancing their performance. Contributions, limitations and implications were then discussed.